DRAMATURGY OF STANISLAV-IGNATIUS VITKEVYCH: THE PROUD LONER AND ECCENTRIC - Khorob, Stepan (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article examines the life and work of the outstanding Polish writer, philosopher and artist Stanislav-Ignatius Vitkevych (1885–1939), known under the pseudonym "Vitkatsii". Special attention is paid to his dramaturgy, therefore, accordingly, to his original type of artistic thinking. This reveals the relevance and novelty of the research, because due to this goal, the originality of many components of dramatic art created by the Polish author and Polish theater at that time was clarified. The system of tasks developed on the basis of the goal provides an opportunity to analyze the dramatic works of Stanislav-Ignatius Vitkevych, determining their content and form-creating filling, the originality of the author's ideological and aesthetic consciousness. In accordance with the general concept of the article, the following scientific methods were used: biographical, specific-historical, typological and hermeneutic. The results of the research provide grounds for supporting the opinion about the modernity of the plays of the Polish playwright, his direct involvement in the creation of drama and theater of the absurd in Poland in the first decades of the 20th century. Even more, it was the dramatic works of Stanislav-Ignatius Vitkevych that contributed to the development of the stylistic modification of the pan-European modernist drama of the given period. The practical significance of the study of the peculiarities of the Polish author's drama is that its results can be used both by modern literary and theater scholars, and by Polonist philologists - students, post-graduate students, and scientists in general who study the life and work of Stanislav-Ignatius Vitkevych